Measurement of the triple-differential cross section for photon plus jets production in proton-proton collisions at=7 TeV - Chatrchyan, S. (2014)
A measurement of the triple-differential cross section, , in photon + jets final states using a data sample from proton-proton collisions at = 7 TeV is presented. This sample corresponds to an integrated luminosity of 2.14 fb(-1) collected by the CMS detector at the LHC. Photons and jets are reconstructed within a pseudorapidity range of |eta| < 2.5, and are required to have transverse momenta in the range 40 < < 300 GeV and > 30 GeV, respectively. The measurements are compared to theoretical predictions from the sherpa leading-order QCD Monte Carlo event generator and the next-to-leading-order perturbative QCD calculation from jetphox. The predictions are found to be consistent with the data over most of the examined kinematic region.